Solve for y 4y^2+3y-3=0

Math
4y2+3y-3=0
Use the quadratic formula to find the solutions.
-b±b2-4(ac)2a
Substitute the values a=4, b=3, and c=-3 into the quadratic formula and solve for y.
-3±32-4⋅(4⋅-3)2⋅4
Simplify.
Tap for more steps…
Simplify the numerator.
Tap for more steps…
Raise 3 to the power of 2.
y=-3±9-4⋅(4⋅-3)2⋅4
Multiply 4 by -3.
y=-3±9-4⋅-122⋅4
Multiply -4 by -12.
y=-3±9+482⋅4
Add 9 and 48.
y=-3±572⋅4
y=-3±572⋅4
Multiply 2 by 4.
y=-3±578
y=-3±578
The final answer is the combination of both solutions.
y=-3-578,-3+578
The result can be shown in multiple forms.
Exact Form:
y=-3-578,-3+578
Decimal Form:
y=0.56872930…,-1.31872930…
Solve for y 4y^2+3y-3=0

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top